A trial of inpatient indication based prescribing during computerized order entry with medications commonly used off-label - Walton, S.M.; Galanter, W.L.; Rosencranz, H.; Meltzer, D.; Stafford, R.S.; Tiryaki, F.; Sarne, D. (Applied Clinical Informatics, 2011)
Background: Requiring indications for inpatient medication orders may improve the quality of prescribing and allow for easier placement of diagnoses on the problem list. Indications for inpatient medication orders are also required by some regulators.Objective: This study assessed a clinical decision support (CDS) system designed to obtain indications and document problems during inpatient computerized physician order entry (CPOE) of medications frequently used off-label.Methods: A convenience sample of three medications frequently used off-label were selected: the PPI lansoprazole; intravenous immune globulin, and recombinant Factor VIIa. Alerts triggered when a medication was ordered without an FDA approved indication in the problem list. The alerts prompted clinicians to enter either a labeled or off-label indication for the order. Chart review was used as the gold standard to assess the accuracy of clinician entered information.Results: The PPI intervention generated 873 alerts during 60 days of operation; IVIG 55 alerts during alerts during 93 days; Factor VIIa 25 alerts during 175 days. Agreement between indications entered and chart review was 63% for PPI, 49% for IVIG, and 29% for Factor VIIa. The alerts for PPI, IVIG and Factor VIIa alerts produced accurate diagnoses for the problem list 9%, 16% and 24% respectively. Rates of off-label use measured by chart review were 87% for PPI, and 100% for IVIG and factor VIIa, which were higher than if measured using the ordering clinicians’ indications.Conclusion: This trial of indication-based prescribing using CDS and CPOE produced less than optimal accuracy of the indication data as well as a low yield of accurate problems placed on the problem list. These results demonstrate the challenge inherent in obtaining accurate indication information during prescribing and should raise concerns over potential mandates for indication based prescribing and motivate further study of appropriate mechanisms to obtain indications during CPOE.
Keywords: Testing and evaluation; electronic health records and systems; inpatient; inpatient CPOE; medication administration records; exploratory